Editorial (Inglês) - Mota, Maurício (Revista de Direito da Cidade, 2017)
DOI: 10.12957/rdc.2017.29654 The Journal of City Law, a journal classified by MEC / CAPES as Qualis A1, Law and registered in the Web of Science, is pleased to inform all its readers that it was registered in COBISS (Virtual Library of Slovenia), a portal that brings together More than 500 Slovenian libraries, in the Republic of Slovenia, in Eastern Europe (see: http://cobiss6.izum.si/scripts/cobiss?command=DISPLAY&base=99999&rid=525904409&fmt=11&lani=si). In this issue of the Journal we have also broadened our body of our reviewers / evaluators, with the inclusion of many Professors from many States of the country and many foreign professors. We also publish, for the immediate consultation of readers, the links of the various national and international indexes of Journals and periodicals where our Journal of City Law is indexed. We thank, as always, all the readers, authors, evaluators and collaborators for the collaboration and trust and for the always excellent work done. We always remind you that the submissions to the Journal of City Law are permanent and must be carried out by the system, directly on the Journal’s page.